The effect of moisture and methods of breaking seed dormancy on germination of Mimusops elengi - Abas, Asmah Husna (2015)
Mimusops elengi is a crop which often planted as an ornamental and shade tree in gardens and along roads, also in coastal sites. This plant also has valuable value as medicinal plant which has been used for treat diseases. So far in our country, this plant is not exploited commercially for various applications. Malaysia has potential to produce products based on this plant and establish industry which is now abandoned. For establish this industry, need regular supply of the plant. The most important thing is planting materials to continue the production. This crop can be grown both from seeds and cuttings with seeds having preference due to easy handling and transportations. However, the seeds have been reported that the seeds take very long time to germinate when sown. In order to establish a method to store Mimusops seeds, the present study was carried out to determine the effect of desiccation, cryopreservation (-196°C), treatments breaking seed dormancy, and practical way to break seed dormancy on the germination of Mimusops elengi. In the first experiment, Mimusops seeds were desiccated using two methods which are using laminar air flow and silica gel methods. The seeds were desiccated from 34.9% moisture content to 30%, 20%, 15%, 10% and 7% followed by germination on sterilized sand. Results showed that desiccation affect the germinability of Mimusops seeds. For 20% moisture content and above, the percentage of germination is between 11-14% which are low whereas 20% moisture content and below, none of the seeds was germinated within fifty days. In the second experiment, clipped and unclipped seeds desiccated to 30%, 20%, 15%, 10% and 7% moisture content were subjected to liquid nitrogen (-196°C) exposure for 24 hours. Results showed that both clipped and unclipped seeds do not germinate within time of observation (50 days).